BIOEMEPED ANALYSIS OF THE BODY COMPOSITION AND ANTHROPOMETRIC CHARACTERISTICS OF STUDENTS FROM INDIA - Abbas, Syed Ali; AS, Seitova; K.Sh., Sakibaev; G.V, Belov (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Anthropometry for more than 50 parameters and component composition of the body with the help of the bioassayed analyzer ABC-01 "Medass" were studied in 80 first-year students from India (50 young men, 30 girls). The control group consisted of 100 students and 50 female students permanently residing in the city of Osh. Some of the anthropometric figures of visiting students were significantly lower in comparison with the control group, especially among girls. Bioempedance analysis revealed a significant decrease in fat mass parameters, normalized for growth, a proportion of skeletal muscle mass in young men and women of the main groups, and an increase in the specific basal metabolism in young men compared with the control group